DIAGNOSIS OF Fusarium oxysporum FUNGUS ISOLATIONS AND Bacillus BACTERIA THE OF EFFICIENCY THE OF EVALUATION OF INHIBITION THE IN PHOSPHATE POTASSIUM AND subtili - Risan, Mohsen (Iraqi Journal of Science, 2024)
The study aimed to isolate and diagnose types of Fusarium oxysporum from the roots of cucumbers and melons plants infected , from the fields of Al- Ssaouira, Al-Numaniya and Al-Hai in Wasit Governorate , and the possibility to control it by using the bacteria Bacillus subtilis and potassium phosphate concentration (500) mg / liter of water. Were obtained on (19) pure isolates of fungus F.oxysporum f.sp. cucumerinum and (11) pure isolates of F.oxysporum f.sp. melonis . The isolate F.oxysporum f.sp. cucumerinum (FOS 9) showed a high virulence than the rest isolates , white the isolates F.oxysporum f.sp. melonis (FOM 2) showed a high virulence than the rest isolates . The bacteria B.subtilis showed high antibiosis activity against F. oxysporum f.sp. cucumerinum and F.oxysporum f.sp. melonis and recorded (87.0%) and (92.5%) respectively.